Relational ties or customized contracts? An examination of alternative governance choices in China - Zhou, Kevin Zheng; Poppo, Laura; Yang, Zhilin (Journal of International Business Studies, 2008)
As business transactions become more complex in China – an increasingly market-driven economy – are managers more likely to employ relational ties or contracts? Consistent with the view that personal institutions govern transactions in China, our analysis of 361 buyer–supplier exchanges indicates that managers rely more on relational ties as asset specificity and uncertainty increase. We also find some support that impersonal institutions govern market transactions: as uncertainty increases, managers craft more customized contracts. Surprisingly, there is no association between contracts and asset specificity. These results hold for both local and foreign firms.